(untitled) (Вісник Кримінологічної асоціації України, 2022)
The article is devoted to the study of the heuristic path of criminological cognition. As a result the purposeful expression of specific ideas by a criminologist triggers the processes of functional self-organization of the criminological discourse system. There the semantic components are accumulated and integrated into a single multidimensional criminological space.